"So you're saying": the interrogation of Jordan Peterson - Barry Pennock-Speck (Revista de Lingüística y Lenguas Aplicadas)
In this article, I analyse the infamous Cathy Newman interview with Jordan Peterson on the 16th of January 2018 and subsequent viewer comments on Channel 4's YouTube channel. My first hypothesis is that Newman's frequent attribution of statements to Peterson using the now notorious "so you are saying" gambit (YSG) is what triggered outrage among Peterson's followers, which, in turn, generated media interest. My second hypothesis is that the interview is best understood as a series of Face threats by Newman on Peterson using the YSG. To ascertain if my hypotheses are true, I performed corpus linguistic analyses on the interview and comments to provide objective descriptions of both.  Episodes in which the YSG were used were identified and analysed using Goffman's (1967) Facework approach. My analysis shows that the YSG was indeed a salient feature of the interviewer's discourse and was used to attack the interviewee's Face.